Pengaruh Promosi dan Brand Image terhadap Keputusan Pembelian Pada E-Commerce Lazada Indonesia: (Studi di Kabupaten Badung) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the impact of advertising and brand image on Lazada Indonesia e-commerce purchasing decisions. The research methods used are quantitative. Badung's research site. The sample consisted of 100 of his respondents. The data analysis techniques used are plausibility tests, reliability, classical assumptions, multiple regression, coefficient of determination, t-tests, and F-tests. Based on the results of the research, advertising has a significant positive impact on purchasing decisions, brand image has a significant positive impact on purchasing decisions, and at the same time, advertising and brand image have a positive and significant impact on purchasing. It turns out. decision. The influence of independent variables on purchase decisions is 60%. Here are some suggestions from this survey: Commerce Lazada Indonesia will regularly update its website or application to make its promotions more attractive, reprimand or sanction merchants found to be deceiving consumers, and rebuke or sanction products that do not match product descriptions. must be provided.